Analysis of Passenger Satisfaction with LRT Jakarta Services Route Velodrome - Boulevard Utara - Muhammad Isradi; Muhammad Naufal Farhan; Andri Irfan Rifai; Amar Mufhidin; Joewono Prasetijo (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
One of the problems in the city of Jakarta is traffic jams which cause losses of up to 36 trillion rupiah per year. The efforts of the local government to unravel vehicle congestion are the construction of rail-based public transportation such as KRL, MRT and LRT which is integrated with public transportation in other cities. One of them is the new public transportation operating, namely the LRT (Light Rail Transit). In realizing the public transportation system in the city of Jakarta, it is hoped that the community will switch from private vehicles to integrated public transportation so that the Jakarta LRT manager must provide the best service in the operation of the Jakarta LRT. The objective of this research is to find out the level of service quality provided to consumers, it is necessary to analyze the quality of service so that people want to switch to using public transportation from private vehicles so as to reduce the number of vehicles on Jakarta city roads. In this analysis, it discusses the satisfaction of LRT passengers in Jakarta Velodrome Route - North Boulevard by comparing service performance and service satisfaction then processing it using the "Importance Performance Analysis" method so that we can find out the position of service factors according to priority levels based on the quadrants in the Cartesian diagram, then analyze it with the Validity Test, Reliability Test and Normality Test with a sample size of 100 respondents using the SPSS program. The results of the analysis show that service performance and passenger service satisfaction get an average rating achievement, for service performance of 4.08 out of 5.00 (very good) and service satisfaction of 4.13 out of 5.00 (very satisfied). The results of the validity test obtained more than 0.165 (valid data), the results of the Reliability test obtained Cronbach's Alpha results of more than 0.6 (reliable data) and the results of the normality test were more than 0.5 (data normally distributed).